ROCK TYPE RESERVOIR CHARACTERIZATION OF 34-2 SANDSTONE INTERVAL AT TALANG AKAR FORMATION, ASRI BASIN - GUNAWAN, HERI
Production profile of 34-2 interval at Widuri Field has reached its peak in 2001-2002 and started in brown field phase. Therefore, it needs field development works in order to maintain production performance such as update reserve calculation as based of water injection program. This program needs detailed analysis of facies and facies association, for further works of static reservoir modeling through rock typing so that reservoir petrophysics distribution could be better understand. The several data which used in this research are core data at four wells with total length of 430 ft, core plug at 101 points, 152 well log data, and 3D seismic data. The first step is identification of facies and facies association in order to predict depositional environment. 34-2 interval reservoir is consist of two facies association; barrier bar and fluvial-estuary sandstones, which deposited in different time. The early deposition is barrier bar which deposited in transgression phase then incised valley formed due falling of sea level and its valley filled by fluvial-estuary deposit. Rock Type is identified based on pore throat size through Windland R35 approach, which constrained by facies association and controlled by lithofacies. Four RT are identified as (1) RT1 – Very coarse-coarse through cross bedding sandstone (St) and Coarse-medium through planar bedding sandstone (Sp), (2) RT2 – Medum-fine horizontal lamination sandstone (Sh), (3) RT3 – Fine-very fine flaser sandstone (Sf), and (4) RT4 – Fine-coarse bioturbated sandstone (Sb). The reservoir quality series from good to poor are RT1, RT2, RT4, and RT3. 3D Reservoir characterization is done through modeling of facies, RT, porosity (controlled by RT), and permeability (which controlled by RT and porosity). Barrier bar sandstone deposit is consist of four RT i.e; RT1, RT2, RT3, and RT4 meanwhile fluvial-estuary channel sandstone deposit is consist of three RT i.e; RT1, RT2, and RT3.